Implementasi Omnichannel Marketing untuk Meningkatkan Pengalaman Pelanggan pada Showroom Aes Motor - Agustin, Novi; Isyanto, Puji (LANCAH: Jurnal Inovasi dan Tren, 2024)
The implementation of omnichannel marketing at AES Motor showroom aims to improve customer experience through effective integration of communication channels. Consumers now conduct marketing interactions through various channels, including physical stores and gadgets, to evaluate products, compare prices, and conduct digital transactions. Omnichannel marketing helps improve customer satisfaction by integrating multiple communication channels, such as physical stores, websites, chat apps, and customer service. This research focuses on how omnichannel marketing can improve the customer experience at the AES Motor showroom, as well as how this strategy can help improve customer loyalty and increase sales. The purpose of this research is to create a conceptual model that can help scholars and practitioners understand the dynamics between omnichannel marketing and customer experience. The results are also expected to provide information on how best to implement integration strategies and provide strategic advice for businesses in the used car retail industry.